Who gets a laboratory positive diagnosis of Mycoplasma pneumoniae: A 10-year retrospective analysis - Charlotte Patterson (Clinical Infection in Practice, 2021)
Objectives: Mycoplasma pneumoniae (M. pneumoniae) is thought to cause up to a third of community acquired pneumonias (CAP), but may be undiagnosed due to limitations with current diagnostics, and untreated given the frequent use of B-lactams to which M. pneumoniae is not susceptible. We performed a ten-year retrospective analysis to identify the typical characteristics of a patient with a laboratory positive diagnosis of M. pneumoniae. Methods: Laboratory diagnosis of M. pneumoniae was performed using Polymerase Chain Reaction (PCR) and Serology (passive particle agglutination (PPA) and Enzyme-linked immunosorbent (EIA) assays). Data were collected on all patients tested for M. pneumoniae between 2009 and 2019. Results: 19,090 PCR and 4530 serology samples were tested for M. pneumoniae with 278 positive results. The positive group had a median age of 40 years (interquartile range 30–41 years); Median C-reactive Protein (CRP) was 71 mg/L, White blood Cell Count (WBC) 7 × 109. 80% had an abnormal Chest X-ray. Intensive Care Unit (ICU) admission occurred in 4.5%; 1.3% patients died. 29% of patients were positive on both serology and PCR testing platforms. Conclusions: The characteristics reported here could be used as guidance on who is treated for M. pneumoniae. We propose that testing for M. pneumoniae needs to be performed systematically in patients with CAP; and that targeted atypical pathogen cover should be considered in preference to B-lactam mono-therapy for all patients with these characteristics.